Novel strategies of coagulation inhibition for reducing tumor growth and angiogenesis. Issue 164 (April 2018) - Nadir, Yona; Brenner, Benjamin
Abstract: Activated proteins of the coagulation system are known to enhance angiogenesis and tumor growth. Notably, the main coagulation proteins involved are those of the extrinsic and common pathways. Strategies to attenuate tumor progression by decreasing activation of the coagulation system may be compromised by an increased risk of bleeding. Currently, studies using derivatives of heparins devoid of or with low anticoagulant activity are being conducted. Heparanase protein was demonstrated to enhance tissue factor activity. In-house developed peptides, deriving from tissue factor pathway inhibitor 2 (TFPI-2) were shown to inhibit heparanase procoagulant activity by interrupting the interaction between TF and heparanase. These peptides appeared to have a non-hemostatic anti-angiogenic effect. In a mouse model, the peptides caused a significant reduction in tumor growth and relapse, without predisposing to bleeding. Hence, the effects of these inhibitory peptides in cancer patients may deserve further investigation in clinical research studies.